Omalizumab in the treatment of asthma. (December 2011) - Tan, Ricardo; Corren, Jonathan
Omalizumab was introduced in 2003 and is the first asthma drug to target IgE, the allergic antibody that initiates the allergic cascade. Well-controlled studies and post-marketing clinical experience have shown it to be an effective and safe medication. Treatment guidelines now recommend omalizumab as an add-on option for patients with moderate-to-severe allergic asthma uncontrolled on high-dose inhaled corticosteroids and long-acting ββ-agonists. Despite initial concerns, there is no evidence of any association with malignancy at this time. In our opinion, omalizumab is well-tolerated and significantly improves pulmonary function, decreases clinical symptoms and improves the quality of life in patients with uncontrolled allergic asthma.